Effects of plyometric jump training on soccer player`s balance: A systematic review and meta-analysis of randomized-controlled trials - Clemente, F. M.; Ramirez-Campillo, R.; Castillo, D.; Raya-González, J.; Rico-González, M.; Oliveira, R.; Rosemann, T.; Knechtle, B. (Biology of Sport, 2022)
Plyometric jump training (PJT) can be used for improving balance through bilateral and unilateral jump-landing drills. Since the increased number of articles testing the effects of PJT on dynamic and static balance, it is relevant to summarize the evidence and determine the effects across different original articles. This systematic review with meta-analysis was conducted to assess the effects of PJT programs on dynamic and static balance in soccer players. The data sources utilized were Cochrane, Medline (PubMed), SPORTDiscus, and Web of Science. (i) Soccer players of any age or sex without injury, illness, or other clinical conditions; (ii) PJT-based programs restricted to a minimum of three weeks (duration); (iii) passive or active control groups; (iv) pre-post interventions values of dynamic and/or static balance; (v) randomized-controlled trials; and (vi) peer reviewed original full-text studies written in English, Portuguese, and/or Spanish. The database search initially identified 803 titles. From those, eight articles were eligible for the systematic review and meta-analysis. The results showed no significant differences between PJT and active controls in dynamic anterior, postero-medial, or postero-lateral balance for both left and right legs (p > 0.05). Additionally, no significant differences were found between PJT and active controls in terms of static balance (p = 0.495). The current evidence suggests that PJT has no significant advantage over active control groups in terms of dynamic or static balance.